2008
DOI: 10.1371/journal.pone.0003562
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Epithelial Immune Cell Transfer during Suckling Modulates Delayed-Type Hypersensitivity in Recipients as a Function of Gender

Abstract: IntroductionBreast feeding has long term effects on the developing immune system which outlive passive immunization of the neonate. We have investigated the transfer of milk immune cells and examined the result of transfer once the recipients were adult.MethodsNon-transgenic mouse pups were foster-nursed by green fluorescent protein (GFP) transgenic dams for 3 weeks and the fate of GFP+ cells was followed by FACS analysis, immunohistochemistry and RT-PCR for GFP and appropriate immune cell markers. Pups suckle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 25 publications
4
40
0
3
Order By: Relevance
“…However, our results, showing that orally ingested PTX3 is rapidly accumulated in tissues, are in favor of a transfer from mother to neonate during breastfeeding via the gastrointestinal tract, as reported for other molecules (16). Milk cells can also migrate through the gastrointestinal barrier of neonates and accumulate in different organs (44), as reported in mice and sheep (16,44,54). This phenomenon is suspected to occur also in humans (16,55,56).…”
Section: Discussionsupporting
confidence: 79%
“…However, our results, showing that orally ingested PTX3 is rapidly accumulated in tissues, are in favor of a transfer from mother to neonate during breastfeeding via the gastrointestinal tract, as reported for other molecules (16). Milk cells can also migrate through the gastrointestinal barrier of neonates and accumulate in different organs (44), as reported in mice and sheep (16,44,54). This phenomenon is suspected to occur also in humans (16,55,56).…”
Section: Discussionsupporting
confidence: 79%
“…Such maternally inherited T cells, acquired during breastfeeding, protect mice against rejection of semiallogeneic skin grafts (47) and affect delayed-type hypersensitivity (48).…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated dam to pup transfer of milk immune cells and suggested that they conferred short-term, passive, cellular immunity (7–10). However, previous work from this laboratory, showing persistence of lactationally-transferred immunity to adulthood (11), suggested the existence of a more active mechanism through which transferred cells instructed development of the neonate’s T cell repertoire. Here we provide evidence in support of such a mechanism.…”
Section: Introductionmentioning
confidence: 88%